Perspectivas en holoprosencefalia - Haratz-Rubinstein, Drs. Natan; Monteagudo, Ana; Timor-Tritsch, Ilan E.; Tineo, Rafael (Gaceta Médica de Caracas, 2021)
La holoprosencefalia es una anomalía del desarrollo del cerebro anterior o prosencéfalo causada por una falla en su normal división durante la cuarta semana de gestación (post-ovulatoria). Holoprosencephaly is a complex developmental anomaly of the forebrain or prosencephalon caused by a failure in its normal cleavage during the fourth gestational week (post-ovulatory).